Превентивне затримання: запобіжний або «позапроцесуальний» захід? - Фоміна, Т. Г.; Fomina, T. H.; Тетяна Фоміна (Актуальні проблеми держави і права. – 2019. – Вип. 83. - С. 240-246, 2019)
Визначено сучасні проблеми регламентації порядку превентивного затримання, окреслено проблемні моменти щодо визначення строків превентивного затримання та суб’єктів його здійснення. З’ясовано відмінності між превентивним затриманням та затриманням у порядку ст. 208 КПК України, а також триманням під вартою. Висловлено власний погляд щодо можливого вдосконалення законодавства в частині регламентації порядку превентивного затримання.

Introduction of preventive detention in national legislation in 2014 has caused controversy among lawyers about the expediency of its existence. The author of the article has defined the current problems in the regulation of preventive detention’s procedure; has outlined the problematic issues on determining the terms of preventive detention and the subjects of its implementation; has clarified the differences between preventive detention and detention within the Art. 208 of the Criminal Procedural Code of Ukraine, as well as detention in custody; has expressed own opinion on the possible improvement of the legislation regarding the regulation of preventive detention’s procedure. It has been concluded that preventive detention’s procedure requires to be reviewed at the legislative level. The systematic analysis of the provisions of the Criminal Procedural Code of Ukraine and the Law of Ukraine “On Combating Terrorism” demonstrated the fact of their inconsistency and contradiction. Besides, consolidation of preventive detention raises doubts about the legality of its regulation and raises questions about the conformity of the legislative provisions on terms and the procedure for its implementation to the Constitution of Ukraine. The procedure for this type of detention at the legislative level is virtually undefined, and substatutory regulation of this institution is imperfect. The author has expressed her conviction that it is expedient to align the provisions of the Art. 15-1 of the Law of Ukraine “On Combating Terrorism” with the provisions of the Constitution of Ukraine and the Criminal Procedural Code of Ukraine in the conditions of hostilities in the East of Ukraine and conduction of anti-terrorist operation. Such a way is possible only if the Criminal Procedural Code of Ukraine determines preventive detention as the type of preventive measures; determining the reasons for such detention; regulation of the procedure for its implementation, with reference to the subjects of direct detention and the subjects of subsequent decision-making on detention in custody within criminal proceedings. Provisions on the terms of preventive detention and the subjects who make decisions on detention in custody for more than 72 hours also need to comply with the Art. 29 of the Constitution of Ukraine.

Определены современные проблемы регламентации порядка превентивного задержания, обозначены проблемные моменты определения сроков превентивного задержания и субъектов его осуществления. Выяснены отличия между превентивным задержанием и задержанием в порядке ст. 208 УПК Украины, а также содержанием под стражей. Выражена собственная точка зрения о возможном совершенствовании законодательства в части регламентации порядка превентивного задержания.
Preventive detention: is it preventive or “non-procedural” measure?
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; запобіжний захід; precaution; мера пресечения; превентивне затримання; preventive detention; превентивное задержание; тримання під вартою; custody; содержания под стражей; законодавство; legislation; законодательство; антитерористична операція; anti-terrorist operation; антитеррористическая операция; боротьба з тероризмом